Psychometric evidence of the Implicit Theories of Intelligence Scale (ITIS) in Peruvian university students - Correa-Rojas, Jossué (2024)
Intelligence is a psychological attribute that has been related to academic performance (Ayoub et al., 2022) and creativity in university students (Sánchez-Cid et al., 2018). In this sense, Dweck et al. (1995) remarked the importance of self-theories or self-perception about one's own intellectual capacity and the belief of whether it can be modifiable, for the achievement and academic success in higher education students. According to Sternberg (1985) theories explaining intelligence have been organized into two categories: implicit and explicit. Implicit theories refer to particular and personal beliefs based on experience and explicit theories emphasize the biological component and the conception of multiple intelligences. In other words, implicit theories of intelligence constitute a self-perception about one's own intellectual capacities. In this regard, studies have demonstrated their importance in the educational field, as they are related to motivation, academic performance and general well-being; however, despite the fact that empirical evidence has demonstrated the importance of implicit theories of intelligence in the field of higher education (Costa & Faria, 2018), in Peru there is no valid and reliable measure to fill the existing knowledge gap on this subject. Therefore, the main purpose of this research was to analyze the psychometric evidence of the Implicit Theories of Intelligence Scale (ITIS) (Dweck, et al., 1999). The study is framed in an instrumental design, for which 1319 university students were selected, through a non-probabilistic sampling, with the average age of the participants being 20 years old, most of them being women (57.1 %). Initially, the ITIS statements were translated into Spanish, the relevance of the linguistic adaptation was reviewed through the back translation procedure recommended by the International Test Commission (2005). Then, the version translated into Spanish was applied on a sample of 319 participants with whose data the Exploratory Factor Analysis (EFA) was performed, the results showed that the translated version replicates the structure originally proposed by Dweck et al. (1995). Subsequently, on a sample of 1000 participants, this two-dimensional structure was corroborated in which the Entity Theory (ET) and the Incremental Theory (IT) were differentiated. A Confirmatory Factor Analysis (CFA) was carried out with the method of unweighted least squares with mean and variance adjusted (WLSMV). The results showed that of the three models tested (Model 1, original model; Model 2, with correlated errors; Model 3, reduced version) the second model in which errors are established between items 1 and 2 and 7 and 8 is the one with the best fit indices (CFI = .993; TLI = .987; RMSEA = .047 [.027 - .068]); also, its internal structure is solvent and invariant according to sex. On the same sample (n = 100), validity was analyzed in relation to other constructs and it was determined that the TE is negatively related to Consistency of Interest (CI), Academic Self-Efficacy (AA) and Dispositional Optimism (OD), while the TI is positively related to Perseverance Effort (PE), AA and OD. The reliability of the ITIS was determined by internal consistency, both factors reported optimal omegas coefficients (TE, ω = .786; TI, ω = .741); in addition, the measure showed temporal stability in its scores after two weeks with respect to the first application (CCI = .751 for TE and CCI = .761 for TI). In sum, the ITIS is a measure that presents adequate evidence of validity and reliability in Peruvian university students; its scores are consistent, interpretable and invariant according to sex.